Effectivity of progressive taxation from the micro- and macroeconomic perspective - Alena Zubal'ová; Martin Geško; Michal Borza (DANUBE: Law, Economics and Social Issues Review, 2020)
Many empiric analyses on the topic of the progression exist and despite their often contradictory results governments still include their conclusions in to their tax policies. Many questions arise in relation to the issue: What is the theoretical justification of progressive taxation? What are the effects of the progression from the microeconomic and macroeconomic perspectives? Which conditions should be met in the real-world for progressive taxation to be effective? The purpose of the article is to find the answers to these questions. We aim to identify a set of requirements that shall be observed if the efficiency of progressive taxation in real conditions is the goal. We conclude that the taxation as a built-in stabilizer have an impact on economic stability under certain conditions. We described the mechanism of how the taxation act in the counter-cyclic and pro-social way and we defined the factors which influence the efficiency of progressive taxation in the real economy.
Keywords: 330; Personal Income Tax; Ability to Pay; Progressivity; Automatic Stabilizers; Fiscal Policy